Terrorism and Capital Markets: The Effects of the Istanbul Bombings - Nikos Christofis; Christos Kollias; Stephanos Papadamou; Apostolos Stagiannis (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Beyond the loss of life and personal injuries that the victims of terrorist actions suffer and the atmosphere of fear terrorists seek to create with their premeditated use of brutal violence, terror also has real economic and political costs that go beyond the immediate costs and damages of a terrorist attack. Terrorist actions can have a multitude of economic consequences that may adversely affect a number of economic indices, sectors and activities including their impact on capital markets. This paper sets out to examine the effect of these attacks on the Turkish Stock Market. It focuses its empirical investigation on the Istanbul stock-market and the impact that recent major terrorist incidents exerted on market behaviour. Findings reported herein indicate in some cases significant abnormal returns.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: G14; G21; C22; 330; terrorism; capital markets; conditional volatility